2010
DOI: 10.1158/1541-7786.mcr-09-0494
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulates Keratin 8 Homeostasis in Mammary Epithelial Cells and in Breast Tumors

Abstract: Autophagy is activated in response to cellular stressors and mediates lysosomal degradation and recycling of cytoplasmic material and organelles as a temporary cell survival mechanism. Defective autophagy is implicated in human pathology, as disruption of protein and organelle homeostasis enables disease-promoting mechanisms such as toxic protein aggregation, oxidative stress, genomic damage, and inflammation. We previously showed that autophagy-defective immortalized mouse mammary epithelial cells are suscept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…Concomitantly, the autophagy-promoting activity in the MCF7 breast cancer cell line following transfection with Beclin-1 was observed to inhibit MCF7 proliferation, clonogenicity and tumorigenesis (10). A previous in vivo study demonstrated that mice with inactivated or deleted Beclin-1 were susceptible to tumors including lymphoma, lung cancer and liver cancer (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly, the autophagy-promoting activity in the MCF7 breast cancer cell line following transfection with Beclin-1 was observed to inhibit MCF7 proliferation, clonogenicity and tumorigenesis (10). A previous in vivo study demonstrated that mice with inactivated or deleted Beclin-1 were susceptible to tumors including lymphoma, lung cancer and liver cancer (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, the autophagy-promoting activity in the MCF7 breast cancer cell line following transfection with Beclin-1 was observed to inhibit MCF7 proliferation, clonogenicity and tumorigenesis (10). A previous in vivo study demonstrated that mice with inactivated or deleted Beclin-1 were susceptible to tumors including lymphoma, lung cancer and liver cancer (11,12).Beclin-1 modulates cancer initiation and progression by affecting a wide range of pathological events, including extracellular matrix degradation, epithelial-to-mesenchymal transition, tumor angiogenesis and alterations to the tumor microenvironment (13). However, the effect of Beclin-1 in cancer development is complex, as a number of reports have indicated the pro-neoplastic and anti-neoplastic functions for Beclin-1, as reviewed by Ozpolat and Benbrook (14).…”
mentioning
confidence: 99%
“…Additionally, it may also contribute to breast cancer development in a manner independent of genotoxic stress and genomic instability through the induction of ER stress. Based on a study of Kongara et al [32] in 2010, autophagy plays a role in p62-dependent keratin 8 homeostasis in mammary epithelial cells and low Beclin-1 Figure 3. Autophagy and some of its regulatory pathways Binding of insulin or growth factors to the insulin receptor triggers the PI3K pathway, converting PIP2 into PIP3 that recruits PDK1 and Akt to the plasma membrane.…”
Section: Autophagy and Breast Cancermentioning
confidence: 99%
“…Similarly, the keratin cytoskeleton in mammary epithelial cells disintegrates under metabolic stress of glucose and oxygen deprivation, which mimicks the tumor microenvironment (Nelson et al, 2004) Phosphorylation of CKs regulates their distribution into an insoluble filamentous cytoskeletal fraction and a soluble cytosolic hyperphosphorylated pool (Omary et al, 2006) and plays a role in CK ubiquitination and turnover by the proteasome (Ku & Omary, 2000;Jaitovich et al, 2008) and, likely, by autophagy (Kongara et al, 2010). CKs released from proliferating or necrotic/apoptotic cells are useful markers for prediction of tumor progression/recurrence or response to therapy (Linder, 2007).…”
Section: Biomarkers and Crcmentioning
confidence: 99%